External fixator immobilization after extensor mechanism reconstruction in total knee arthroplasty - Colin D. Canham, MD; Christopher Walsh, MD; Stephen J. Incavo, MD (Arthroplasty Today, 2018)
Extensor mechanism disruption after total knee arthroplasty is a complicated problem that typically requires surgical reconstruction. After extensor mechanism failure, reconstruction is typically indicated to restore active knee extension and provide a stable limb for ambulation. Immobilization of the knee in extension is vital in the initial postoperative period after extensor mechanism reconstruction. We describe a series of 4 patients who underwent extensor mechanism reconstruction followed by external fixator application to maintain the knee extended in the initial postoperative period. Our results have been favorable. However, close follow-up is important to monitor for the development of pin site infections.